More sweetness, fewer calories - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Researchers at the Dutch Institute for Plant Breeding and Reproduction Research (CPRO-DLO) have produced an entirely new crop: the Fructanbeet . This is a sugar beet, which has been genetically modified to produce fructans, sucrose polymers used in...